Evaluation of carbon-11-labelled phenoxy bridged fatty acids for studying myocardial fatty acid metabolism with PET - Groot, Tjibbe de; Maris, Bart; Boonen, Carine; Bormans, Guy; Mortelmans, Luc; Eisenhut, Michael; Verbruggen, Alfons (Nuclear medicine and biology, 1997)
A phenylene moiety in the chain of fatty acids was expected to impair metabolic degradation. Three phenoxy-containing [11C]carboxyl-labelled fatty acids were synthesised and evaluated in mice in an in vivo tissue distribution study. Of these three, 1-[11C]-3-(p-dodecyloxyphenyl)propionic acid (C12C3) showed the most favourable uptake in the myocardium: 1.2% of the injected dose at 30 min p.i., vs. 0.6% for [11C]palmitate. The metabolic stability of C12C3 and [11C]palmitate was assessed by determining the amount of exhaled [11C]CO2 during a 30-min interval after injection. It was found that the phenoxy moiety in the γ-position did not prevent the metabolic degradation of C12C3: After 30 min 20.7% of the injected dose was exhaled as [11C]CO2 vs. 12.7% for [11C]palmitate.
Elektronische Reproduktion der Druck-Ausgabe 24. Dezember 2002
Gesehen am 05.12.2024